I choose, therefore I like: preference for faces induced by arbitrary choice. - Koyo Nakamura; Hideaki Kawabata (PLoS ONE, 2013)
Behavioral choice alters one's preference rather than simply reflecting it. This effect to fit preferences with past choice, is known as "choice-induced preference change." After making a choice between two equally attractive options, one tends to rate the chosen option better than they initially did and/or the unchosen option worse. The present study examined how behavioral choice changes subsequent preference, using facial images for the choice options as well as blind choice techniques. Participants rated their facial preference for each face, and chose between two equally preferred faces and subsequently rated their facial preference. Results from four experiments demonstrated that randomly chosen faces were more preferred only after participants were required to choose "a preferred face," (in Experiment 1) but not "an unpreferred face," (in Experiment 2) or "a rounder face" (in Experiment 3). Further, preference change was still observed after participants were informed that choices were actually random (in Experiment 4). Our findings provide new and important implications characterizing the conditions under which random choice changes preference, and show that people are tempted to make a biased evaluation even after they know that they did not make the choice for themselves.